Gate modulation enhanced position-sensitive detectors using graphene/silicon-on-insulator structure. (30th October 2021) - Jiang, Hao; Fu, Jintao; Nie, Changbin; Sun, Feiying; Tang, Linlong; Sun, Jiuxun; Meng zhu,; Shen, Jun; Feng, Shuanglong; Shi, Haofei; Wei, Xingzhan
Abstract: In this paper, a position-sensitive detector (PSD) with an enhanced position detection performance has been proposed using graphene-silicon-on-insulator (GSOI) structure. By introducing the gate manipulation, the separation efficiency and diffusion speed of the photo-induced charges have been greatly improved. We experimentally observe a 10-fold increase in the generated photocurrent and the response time is shorten by around 8 times, compared to the counterpart without modulation. High position sensitivity (518 μA/mm) to weak-light-sensing, long-distance-sensing (1.2 mm) and good linearity (nonlinearity <2%) are also achieved. The proposed device concept also provides a guidance to improve the performance of other kind of two-dimensional materials based PSDs. Graphical abstract: A new kind of position-sensitive detector (PSD) with an enhanced position detection performance has been proposed using graphene/silicon-on-insulator (GSOI) structure. By introducing the gate manipulation, the separation and subsequent diffusion of photogenerated carriers would be promoted, which produce a positive effect on the photocurrent enhancement and the expansion of detection range. The GSOI PSDs exhibit an outstanding position sensitivity up to 518 μA/mm, a good nonlinearity of no more than 2%, and an extended detection range of 1.2 mm. A 10-fold increase of the generated photocurrent was observed and the response time was shortened by 8.22 times, compared to the counterpart without modulation. These results confirm a vital role of manipulating gate-induced carriers in PSDs and pave an alternative way to explore new optoelectronic conversion devices. Image 1